How often is occult atrial fibrillation in cryptogenic stroke causal vs. incidental? A meta-analysis - Chaisinanunkul, Napasri; Khurshid, Shaan; Buck, Brian H.; Rabinstein, Alejandro A.; Anderson, Christopher D.; Hill, Michael D.; Fugate, Jennifer E.; Saver, Jeffrey L. (Frontiers in Neurology, 2023)
Introduction: Long-term cardiac monitoring studies have unveiled low-burden, occult atrial fibrillation (AF) in some patients with otherwise cryptogenic stroke (CS). But occult AF is also found in some individuals without a stroke history and in patients with stroke of known cause (KS). Clinical management would be aided by estimates of how often occult AF in a patient with CS is causal versus incidental. Methods: Through systematic search, we identified all case-control and cohort studies applying identical long-term monitoring techniques to both CS and KS patients. We performed a random-effects meta-analysis across these studies to determine the best estimate of the differential frequency of occult AF in CS and KS among all patients, and across age subgroups. We then applied Bayes’ theorem to determine the probability that occult AF is causal or incidental. Results: The systematic search identified 3 case-control and cohort studies enrolling 560 patients (315 CS, 245 KS). Methods of long-term monitoring were implantable loop recorder in 34.9%, extended external monitoring in 63.2%, and both in 0.4%. Crude cumulative rates of AF detection were: CS 47/315 (14.9%) versus KS 23/246 (9.3%). In formal meta-analysis, the summary odds ratio for occult AF in CS vs KS in all patients was 1.80 (95%CI 1.05-3.07), p=0.03. With application of Bayes theorem, the corresponding probabilities indicated that, when present, occult AF in CS patients is causal in 38.2% (95%CI 0-63.6%) of patients. Analyses stratified by age suggested that detected occult AF in CS patients was causal in 62.3% % (95CI 0-87.1%) of patients under age 65y and 28.5% (95CI 0-63.7%) of patients age 65 and older, but estimates had limited precision. Conclusions: Current evidence is preliminary, but indicates that in cryptogenic stroke, when occult AF is found, it is causal in about 38.2% of patients. These findings suggest that anticoagulation therapy may be beneficial to prevent recurrent stroke in a substantial proportion of patients with CS found to have occult AF.